2011
DOI: 10.1111/j.1750-2659.2011.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of neuraminidase inhibitor chemoprophylaxis in controlling nosocomial influenza: an observational study

Abstract: Please cite this paper as: Higa et al. (2012) Role of neuraminidase inhibitor chemoprophylaxis in controlling nosocomial influenza: an observational study. Influenza and Other Respiratory Viruses 6(4), 299–303. Background  An influenza outbreak might result in disruption of services at acute care setting hospitals. Objectives  In this study, we retrospectively evaluated the use of neuraminidase inhibitor chemoprophylaxis for prevention of nosocomial spread of influenza in a university hospital. Patients/Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…7 A recent study demonstrated the role of neuraminidase inhibitors in preventing the spread of nosocomial influenza between patients. 28 In summary, nearly one-tenth of hospitalized children with pH1N1 in Australia acquired the infection in healthcare settings. Children with underlying medical conditions were at greater risk of developing nosocomial pH1N1.…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent study demonstrated the role of neuraminidase inhibitors in preventing the spread of nosocomial influenza between patients. 28 In summary, nearly one-tenth of hospitalized children with pH1N1 in Australia acquired the infection in healthcare settings. Children with underlying medical conditions were at greater risk of developing nosocomial pH1N1.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoprophylaxis with antiviral therapy can limit the spread of infection during outbreaks or high-risk seasons. Higa and colleagues 101 demonstrated that neuraminidase (NA) inhibitors may be effective at preventing nosocomial transmission of influenza in hospitalized patients. In a study of HSCT recipients who reside in an outpatient residential facility while undergoing treatment, oseltamivir was provided to all residents after several patients were diagnosed with influenza.…”
Section: Prevention and Treatment Preventionmentioning
confidence: 99%
“…Clinical features of patients with influenza ( Figure 4) We evaluated sequential temperatures of inpatients before and after being diagnosing as having influenza infection. Although, there are few reports concerning prophylaxis of nosocomial infection before the out-break of pandemic A H1N1, 10,16 there are many articles concerning the prophylactic use of NIs in nosocomial settings after the outbreak of pandemic A H1N1 ( Table 1). As shown in Figure 4, mean highest temperature was 37.7 « 0.82°C (mean « standard er-ror).…”
Section: Number Of Cases Those Diagnosed In the University Of The Ryumentioning
confidence: 99%
“…1 it is impossible to prevent all nosocomial influenza virus infections. More specifically, the effectiveness of chemoprophylaxis in the hospital setting [4][5][6][7][8][9][10][11][12][13][14][15][16] has not been well established. Chemoprophylaxis for those who have had close contact with index cases may supplement pre-requisite vaccination to control influenza virus infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation